Everything you always wanted to know about puberty -- and shouldn't learn on TikTok : for curious girls - Hong, Gemma; Young, Sophie (Author at Downtown Bookworks Inc.) (Downtown Bookworks, 2022)
Although there IS factual sex education information on TikTok, it's hard to know who is a reputable resource and it's hard to find all together. This book organizes the answers to questions you might be looking for by sources you can trust -- including websites and TedTalks -- written by Gen Z authors.